PENGARUH PERBEDAAN POSISI PENGELASAN TERHADAP KEKUATAN SAMBUNGAN T-Joint PENGELASAN FILLET DENGAN LAS FCAW PADA PLAT MILD STEEL - Jokosisworo, Sarjito (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2010)
To get quality of good weld joint that in scheme of construction welder of hull must be planned about way of welder, way of inspection, welding flux and weld type which would in utilizing. By karna to get quality of good weld of welder engineering at ship must be followed by will have an effect on to end result from welder process and mechanical properties yielded at construction welder process of ship steel which in the end will influence strength of construction weld joint of ship steel. How big the influence can be done with assaying of mechanical properties at steel plate weld joint. Data analysis result of the assaying can be taken a a real conclusion assists in increasing grade and security and safety of weld joint. This research aim to know strength of joint T-join at weld material to influence position of welder at buckling strength, and visually with EDSA. By using low alloy steel containing grade C=0,15%, Si=0,24%, Mn=0,88%, P=0,018%, S=0,034%. Material is given [by] treatment of welder with various position of welder Horizontal ( 2F ), Vertical ( 3F ), Overhead ( 4F) by using weld FCAW ( Flux cord Arc Welding) with electrode E71T-1, Ã˜ cord 1,2 mm, applies gas CO2, Pada joint type Tjoin welder fillet. Method used in this research is experiment method, that is experimental method directly to object. In this case steel ST42 joint Tjoin with Thick plate 8 mm Marine Plate 18 piece weld by using gas CO2.To get research data is applied [by] observation method by using testing machine bending and test EDSA. Data which collected then is analysed difference of result from visual and mechanic assaying. Result of research shows existence of difference from strength of bending and its(the visulisation is especially to level of weave bead formed between differences of position of Horizontal ( 2F ), Vertical ( 3F ), Overhead ( 4F). And level of influence position of welder to strain bending 72,65 %.. At execution of workmanship of construction of welder so it will pays attention to weld joint planning which will be used, and position of welder which will be executed, thereby we can determine position of welder which good to facilitating welder process without neglecting quality from weld joint.